Rapid molecular assay for the evaluation of clove essential oil antifungal activity against wheat common bunt - Valente, Maria Teresa; Orzali, Laura; Manetti, Giuliano; Magnanimi, Francesco; Matere, Antonio; Bergamaschi, Valentino; Grottoli, Alessandro; Bechini, Sara; Riccioni, Luca; Aragona, Maria (Frontiers in Plant Science, 2023)
Common bunt of durum wheat (DW), Triticum turgidum L. ssp. durum (Desf.) Husn., is caused by the two closely related fungal species belonging to Tilletia genus (Tilletiales, Exobasidiomycetes, Ustilaginomycotina): Tilletia laevis Kühn (syn. T. foetida (Wallr.) Liro.) and T. caries (DC) Tul. (syn. T. tritici (Bjerk.) G. Winter). This is one of the most devastating diseases in wheat growing areas worldwide, causing considerable yield loss and reduction of wheat grains and flour quality. For these reasons, a fast, specific, sensitive, and cost-effective method for an early diagnosis of common bunt in wheat seedlings is urgent. Several molecular and serological methods were developed for diagnosis of common bunt in wheat seedlings but at late phenological stages (inflorescence) or based on conventional PCR amplification, with low sensitivity. In this study, a TaqMan Real Time PCR-based assay was developed for rapid diagnosis and quantification of T. laevis in young wheat seedlings, before tillering stage. This method, along with phenotypic analysis, was used to study conditions favoring pathogen infection and to evaluate the effectiveness of clove oil-based seed dressing in controlling the disease. The overall results showed that: i) the Real Time PCR assay was able to quantify T. laevis in young wheat seedlings after seed dressing by clove oil in different formulations, greatly reducing times of analysis. It showed high sensitivity, detecting up to 10 fg of pathogen DNA, specificity and robustness, allowing to directly analyze crude plant extracts and representing a useful tool to speed up the tests of genetic breeding for disease resistance; ii) temperature was a critical point for disease development when using wheat seeds contaminated by T. laevis spores; iii) at least one of the clove oil-based formulations tested was able to efficiently control wheat common bunt, suggesting that clove oil dressing could represent a promising tool for managing the disease, especially in sustainable farming.